2018
DOI: 10.1002/ajhb.23148
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of physical fitness and its correlates in Chinese children and adolescents in Shanghai using the multistage 20‐M shuttle‐run test

Abstract: Objective The aim of this study was to evaluate the effectiveness of a multistage 20‐m shuttle‐run test (20‐m SRT) in assessing the physical fitness of Chinese children and adolescents in Shanghai. Methods A total of 4833 children and adolescents (2437 males and 2396 females, aged 7–17 years) were enrolled in this study. Height, weight, body fat percentage, fat‐free mass, BMI, and skinfold thickness were measured or calculated. The participants were randomly grouped for performing the 20‐m SRT. The maximal oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…The CRF of children and adolescents living in Tibet was determined using the aforementioned 20mSRT-based method. The CRF data from 4,833 children and adolescents aged 7–17 years (2,437 boys and 2,396 girls) living in Shanghai were published in 2018 [ 27 ]. Similarly, the CRF data describing an international population (1,142,026 children and adolescents from 50 distinct countries/regions in Africa, Asia, Europe, Latin America, North America, and Oceania) were published in 2017 [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CRF of children and adolescents living in Tibet was determined using the aforementioned 20mSRT-based method. The CRF data from 4,833 children and adolescents aged 7–17 years (2,437 boys and 2,396 girls) living in Shanghai were published in 2018 [ 27 ]. Similarly, the CRF data describing an international population (1,142,026 children and adolescents from 50 distinct countries/regions in Africa, Asia, Europe, Latin America, North America, and Oceania) were published in 2017 [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…In China, studies have used 20mSRT to measure physical fitness among children and adolescents in the plains region (e.g., Shanghai [ 27 ] and Hong Kong [ 28 ]). In contrast, few reports have been published for China’s plateau areas.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Arriscado, Muros, Zabala and Dalmau [18] found inverse relationships between the percentage of body fat with maximal oxygen uptake ( r = −0.524), lower body explosive strength ( r = −0.400) and speed performance ( r = 0.385), and this may explain why Polish students with more FFM (kg) have better physical fitness than Spanish students. Other studies carried out in China ( n = 4833) also found that VO 2 max was markedly associated with FFM ( p < 0.001) [19].…”
Section: Discussionmentioning
confidence: 83%
“…The subject endeavored to complete the running speed level. The test ended when they could not follow the rhythm to reach the 20 m end line for two consecutive times, and the number of laps completed was recorded [ 45 , 46 ].…”
Section: Methodsmentioning
confidence: 99%